The Music’s Role in Socialization of the Romani in Turkey: “Musician School” Project Example - Helvaci, Ayhan (European Journal of Multidisciplinary Studies, 2016)
The Romani, who are the people always looked from a distance throughout the history, scared and feared, have always been so close and so far away at the same time. It is hard for every society to accept what is not the same with it, the “other”. However, a Project was planned, with the idea of from local to universal, so that The Romani, who can perform the intercultural carrier, transfer their life-style in a fun way through their language with the music they create, could socialize, instead of being seen as the “other”. Within this Project, it is planned that various groups with a certain musical talent, consisting of The Romani, will have a four-year education in different areas of music and will be helped to share their talent with the society. With this Project, The Romani will tell their dreams, sadness, fights, and their nonchalance of life and their forgotten lives that no one doesn’t want to see or could not see through their songs and dances, which comes from the assumption that it will contribute their unity with society. The artistic activities of the Romani, who are different color in our country, having a rich cultural variety, should be supported. That the natural ability to music and dance in the Gypsies are not limited within them, and that these talents are turned into productivity in different areas of music will both support their development and increase their social value. In this study, Bursa Metropolitan Municipality Conservatory “Musician School” (Çalg?c? Mektebi) Project, designed in 2011 within the scope of music’s role in socialization of the Romani, is examined and it is aimed to present this Project.